Benarkah Dewasa Madya Mempersepsikan Berita Kesehatan di Internet sebagai Berita yang Kredibel? - Cindy Tiara Putri; Ignasia Geralda Vania; Naomi Marsha Abigail Mamarimbing; Whisnu Yudiana (Universitas Andalas, 2021)
The increasing use of social media is followed by the rising spread of fake news. This phenomenon often occurs among middle adults, who usually share the news they receive without knowing the credibility of the news. Looking at the news features is one way to judge its credibility. This study aimed to identify the effect of news’ features, especially the news platform, and supporting data on the news credibility perception in middle adults. This study used an experimental approach with a factorial design. The participants in this research were 120 middle-aged social media users who were assigned randomly in four conditions, namely news with supporting data via Whatsapp, news without supporting data via Whatsapp, news with supporting data via Kompas website, and news without supporting data via Kompas website. The data were collected using an online survey and were analyzed using ANOVA. This study found that there was no significant effect of supporting data and news platforms on news credibility perception in participants. This means that they tend to perceive the credibility of the news without considering the existence of supporting data or reliable news platforms. Adults need to be more careful in believing the news and consider the important aspects that characterize credible news.